Low complexity MIMO MMSE iterative detection algorithm - Lou, Xizhong; Zhou, Qian; Chen, Yanmin (2013 22nd Wireless and Optical Communication Conference, 2013)
In order to reduce computational complexity of the minimum mean square error (MMSE) iterative detection algorithm in multiple-input multiple-output (MIMO) systems and to guarantee performance of the system, we propose a Gray-mapping look-up table (GLT) algorithm based on the theory of constellation region division in IEEE802.11n, which has lower complexity in computing the soft iteration information. For the iterative GLT algorithm, it is not necessary to carry out the minimization searches and the calculation of Euclidean distances in calculating the Log-Likelihood Ratio (LLR) of each estimated bit. The LLR can be found by searching a pre-calculated table. The complexity analysis shows that the GLT algorithm has significantly reduced the computations, which is very helpful for the hardware implementation of MIMO iterative detector. And the experimental simulation shows that the bit-error-ratio (BER) performance of the iterative GLT algorithm is the same as that of the iterative detection algorithm without considering soft priori information, and is almost the same as that of the iterative detection algorithm with considering soft priori information.